Aqueous Dispersion of One-Dimensional van der Waals Material Mo6S3I6with the Charge Type of the Hydrophobic Dispersant Tail - Chae, Sudong; Oh, Seungbae; Choi, Kyung Hwan; Jeon, Jiho; Liu, Zhixiang; Wang, Cong; Lim, Changmo; Dong, Xue; Woo, Chaeheon; Asghar, Ghulam; Chang, Jongwha; Nurunnabi, Md; et al. (ACS Applied Bio Materials, 2020)
Aqueous dispersion of van der Waals bonded one-dimensional materials Mo6S3I6 with hydrophobic surfaces has been studied. The surface charge of the dispersed Mo6S3I6 is controlled from negative to positive by the charge type of dispersant tail (anionic, SDS and NaDDBS; cationic, CTAB; nonionic, Poloxamer 407), and through this, it is possible to deposit the dispersed Mo6S3I6 in nanosized by electrophoretic deposition at a desired position. When a flexible device was manufactured by transferring Mo6S3I6, it was confirmed that electrical conductivity can be measured in 40% of elongation and more than 1000 times cyclic test.
Keywords: Aqueous dispersions; Desired position; Electrical conductivity; Electrophoretic depositions; Flexible device; Hydrophobic surfaces; One-dimensional materials; Poloxamer 407; 1D van der Waals materials Mo6S3I6; aqueous dispersion; dispersant design; stretchable device; surface charge control